PENGARUH LINGKUNGAN KELUARGA DAN PEMBELAJARAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA SISWA SMK NEGERI 1 KOTA BIMA: : (ILIN Institute, 2020)
The study aims at discovering (1) the influence of family environment on students’ entrepreneurship interest at SMKN 1 in Bima city, (2) the influence of entrepreneurship learning on students’ entrepreneurship interest at SMKN 1 in Bima city, and, (3) the extent of the influence of family environment and entrepreneurship learning on students’ entrepreneurship interest at SMKN 1 in Bima city. The study employed descriptive quantitative approach to test the theori by conducting field observation and to explain the result of the study as the way it is. Data were collected by emloying questionnaire. Data were analyzed by using descriptive analysis technique, pre-requisite test of inferential statistic analysis.The result of the study reveal that (1) the family environment gives positive and significant influence on students’ entrepreneurship interest at SMKN 1 in Bima city, (2) the entrepreneurship lierning gives and significant influence on students’ entrepreneurship interest at SMKN 1 in Bima city, (3) the family environment and students’ entrepreneurship interest collaboratively give positive and significant influence on students’ entrepreneurship interest at SMKN 1 in Bima city, (4) the result of multiple linear analysis indicates that partially and simultaneously the variables of family environment and entrepreneurship learning give positive and significant influence on students’ entrepreneurship interest at SMKN 1 in Bima city.